The Relationship of Readiness for Changes and Self-Organization among Teachers of Higher Education - N.A. Semenova; S.A. Pavlova (Психолого-педагогические исследования, 2023)
The relationship between personal readiness for changes as a psychological state that mobilizes personal resources and self-organization as one of the leading professional competencies of a modern higher education teacher is substantiated. The proposed assumption that readiness for change and self-organization have characteristic interrelations is substantiated. The materials of an empirical study obtained on a sample of teachers from different regions of the Russian Federation aged 30 to 70 years, with teaching experience from 3 to 50 years in the amount of 138 people are presented. The methods “Personal change readiness survey” PCRS (Personal change readiness survey) S. Rolnik, V. Hull, N. Heather, R. Gold (adapted by N.A. Bazhanova, G.L. Bardier); "Technological Readiness Index (TRI)" (A. Parasuraman, K. Colby) adapted by Yu.V. Khlopovsky; questionnaire "Diagnostics of the features of self-organization" (DOS) (A.D. Ishkov); author's questionnaire "Professional competencies of a teacher of higher education" were used. Empirical results indicate a low level of readiness for change and an increased level of self-organization indicators, where the indicator of goal-setting is most pronounced, and the least – correction. Conclusions are drawn about the positive relationship between readiness for change, self-organization and optimism, as well as the inverse correlation of these indicators with the level of discomfort that occurs when using various technical innovations in professional activities. The revealed interrelations of indicators of the studied phenomena allow us to most thoroughly approach the formation of a system of professional competencies of a modern teacher of higher education.